A Study On Mechanical Behaviour Of Lead-Free Solder Using Nanoindentation Test - Ong, Mei Kiem (Universiti Sains Malaysia, 2018)
As the usage of lead components has been limited by Europe Union, replacement Sn-Ag-Cu is investigated and practiced in the electronic manufacturing field. Due to constant push for miniaturization in the electronic package, the strength of solder joint of the electronic component on circuit board is reduced due to the decrease in the contact area. Therefore, enhanced mechanical properties of solder joint by embedding nanoparticles are introduced to support changes in technology. The aim of the study is to investigate the effect of nanoparticles reinforcement into nanocomposite solder on a) microstructure and thickness of intermetallic compound layer b) hardness and elastic modulus of the intermetallic compound layer and nanocomposite solder. In this study, 0.05wt% of TiO2, Fe2O3 and NiO nanoparticle is mixed in solder paste respectively. By using surface mounting technology, miniaturized capacitors are placed on printed solder paste on printed circuit board before reflow soldering. Then, samples are prepared in cold mounted sectioned printed circuit board. The mechanical characteristic is measured by using nanoindentation experiment and observation on the sample surface is recorded. The reinforcement of nanoparticles has caused the changes of morphology of IMC layer and 23% - 28% of thickness reduction of the IMC layer. The hardness and elastic modulus of nanocomposite solder are increased by 1 % - 11% and 8% - 31% respectively. In the conclusion, reinforcement of nanoparticles into composite solder has improved the mechanical characteristic of nanocomposite solder and thus strengthen the solder joint.